Utilization of Ultrasonic Sensors as a Robotics Learning Medium in STEM-Based Engineering Education - Khoerunnisa, Ahshonat; Setiawan, Aan Eko; Yuningsih, Siti Hadiaty (International Journal of Ethno-Sciences and Education Research, 2025)
The advancement of robotics technology has supported the integration of efficient navigation systems into STEM-based learning (Science, Technology, Engineering, and Mathematics), particularly in technical and vocational education. One essential component in robot navigation is the distance sensor, with ultrasonic sensors widely adopted due to their ease of integration into project-based learning. This study aims to analyze the performance of three ultrasonic sensors—HC-SR04, HY-SRF05, and RCWL-1601 within the context of Arduino-based microcontroller projects used as educational tools for robotics instruction. Performance analysis was carried out in terms of measurement accuracy, data stability, and response time. The results show that the HY-SRF05 sensor achieved the highest accuracy (96.75%) and the lowest standard deviation (0.23 cm), indicating the most stable performance. The HC-SR04 sensor showed relatively high accuracy but greater data variation, while the RCWL-1601 had the fastest response time but less stable measurements, especially on non-reflective surfaces. These findings can serve as a practical reference for selecting appropriate sensors in project-based teaching activities, particularly in developing robotics learning media that require precision and consistent data. Future research will focus on applying signal processing algorithms such as the Kalman filter and integrating these technologies into technical education curricula.